Age tourism: going beyond health and “triple S” tourism toward a new request of journey - Carrera, Letizia (Frontiers in Sociology, 2025)
For many decades, the large part of developed countries has been experiencing the progressive ageing of their populations. This quantitative change is also accompanied by a qualitative shift in social representations of the third age. Within these changes, a fundamental role is played by the desire to experience opportunities for socializing, leisure, and culture that can shape a new and more complex concept of well-being. Within this context, tourism experience plays a crucial role. The focus is therefore on the new characteristics of senior tourism and the conditions under which it can represent a full and satisfying experience, going beyond the classic offerings of “sun, sand, and sea” or medical tourism. To this end, a qualitative study was conducted, revealing a typology of individuals that can serve as a useful reference for the tourism market to diversifying its offerings.